2013
DOI: 10.1063/1.4805019
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated vertical wind tunnel for the study of sedimentation of non-spherical particles

Abstract: A dedicated 4-m-high vertical wind tunnel has been designed and constructed at the University of Geneva in collaboration with the Groupe de compétence en mécanique des fluides et procédés énergétiques. With its diverging test section, the tunnel is designed to study the aero-dynamical behavior of non-spherical particles with terminal velocities between 5 and 27 ms(-1). A particle tracking velocimetry (PTV) code is developed to calculate drag coefficient of particles in standard conditions based on the real pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 61 publications
0
34
0
Order By: Relevance
“…Finally, secondary motions become fully developed in the Newton's regime (1000 ≤ < 3 × 10 5 ). In addition, in the Newton's regime particle-to-fluid density ratio ′ can significantly affect orientation and secondary motions of particles, and therefore, the drag coefficient [21,22,23,9,46,47,33,15]. Studies on regular-shape particles show that as ′ increases, the secondary motion of particles increases too [22,23,9,33].…”
Section: Surface Roughnessmentioning
confidence: 93%
See 2 more Smart Citations
“…Finally, secondary motions become fully developed in the Newton's regime (1000 ≤ < 3 × 10 5 ). In addition, in the Newton's regime particle-to-fluid density ratio ′ can significantly affect orientation and secondary motions of particles, and therefore, the drag coefficient [21,22,23,9,46,47,33,15]. Studies on regular-shape particles show that as ′ increases, the secondary motion of particles increases too [22,23,9,33].…”
Section: Surface Roughnessmentioning
confidence: 93%
“…projected area of the particle normal to the falling (or flow) direction, [m] , , semi-axes lengths of ellipsoid, a is also the edge length of cuboctahedron, octahedron, cube or tetrahedron, [m] drag coefficient, see Eq. (15) 1−4 empirical expressions used in Eq. (6) , the drag coefficient of a sphere with same volume and Reynolds number as the particle , ℎ diameter and height of cylinder or disk, [m] diameter of a sphere with the same volume as the particle, m e elongation, / % relative error (see Eq …”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Tran-Cong et al [2]; Dellino et al [3]), wind tunnel testing (e.g. Bagheri et al [24]) or by compiling data from the literature, previous authors (e.g. Chhabra et al [1]; Hölzer and Sommerfeld [21]) have found different correlations between C d , Re and particle shape.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
“…In Eq. (2) we disregard all effects due to the pressure gradient, the added mass, the Basset history and the Saffman terms, because we are considering heavy particles: ρ s /ρ g 1 (see Ferry and Balachandar, 2001;Bagheri et al, 2013). Equation (2) has a linear dependence on the fluidparticle relative velocity only when Re s 1, so that φ c 1 and the classic Stokes drag expression is recovered.…”
Section: The Multiphase Flow Modelmentioning
confidence: 99%